Regarding the Current Debate on Aging in Cuba - Alfredo Darío Espinosa Brito (Revista Finlay)
Population aging constitutes one of the achievements and one of the most important challenges in the development of societies. The main cause of aging is the decrease in the fertility of women and to a lesser extent external emigration, especially of young people. In Cuba, more people die than are born, mainly due to low replacement levels in fertility, a situation aggravated in the years of the COVID-19 pandemic. Among the negative consequences of population aging, four main ones are identified: health, economic, sociocultural and legal; among the positive ones, there are some reports of cohorts of people who reach advanced ages in better physical and mental condition. The changes that have occurred in the family institution in many societies and the age discrimination of the elderly have serious consequences for the health, well-being and human rights of the elderly. It is considered that there is a lot of information about the “diagnosis” and “prognosis” of population aging, but there is less about effective actions for its “treatment”, a complex and difficult aspect to face. Some proposals are presented to mitigate these inevitable demographic changes. The purpose of this communication is to comment on certain aspects of the aging of the Cuban population.